All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 131991 by mnjuly1970 last updated on 10/Feb/21
...nicecalculus...provethat:ϕ1=∫01li2(1−x2)=π22−4ϕ2=∫01log(1−t)t341−tdt=π32.2Γ2(34)(log(2)−π2)hint1:ψ(34)=why??easy−γ+π2−3log(2)hint2:ψ(12)=why??easy−γ−2log(2)
Answered by Dwaipayan Shikari last updated on 10/Feb/21
ψ(12)=−γ+∫011−x−121−xdx=−γ+2∫01x−11−x2dx=−γ−2log(2)
I(b)=∫01ta−1(1−t)b−1dt=Γ(a)Γ(b)Γ(a+b)I′(b)=∫01ta−1(1−t)b−1log(1−t)dt=Γ(a)(Γ(a+b)Γ′(b)−Γ′(a+b)Γ(b))Γ2(a+b)putb=12a=14
Terms of Service
Privacy Policy
Contact: info@tinkutara.com